Pemanfaatan Media Sosial YouTube sebagai Media Pembelajaran bagi Siswa Sekolah Dasar - Qurrotul Aini; Agung Setyawan (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The rapid development of information and communication technology has encouraged the integration of digital media into educational practices, including the use of social media as a learning resource. Among various social media platforms, YouTube has become one of the most widely utilized platforms due to its accessibility and diverse educational content. This article aims to examine the utilization of YouTube as a learning medium for elementary school students through a literature review approach. The study employed a qualitative descriptive method using literature review by analyzing relevant books, scientific journal articles, and other academic sources published between 2020 and 2024. The collected literature was analyzed through identification, selection, comparison, and synthesis to obtain comprehensive findings. The results indicate that YouTube provides various benefits in the learning process, including increasing students' learning motivation, improving conceptual understanding through audio-visual presentations, encouraging active learning, and creating a more engaging classroom atmosphere. Nevertheless, its implementation also presents several challenges, such as unrestricted access to inappropriate content, students' dependence on digital devices, and the need for teachers and parents to supervise its use. Therefore, YouTube should be utilized wisely by selecting educational content that aligns with learning objectives. The collaboration between teachers, parents, and schools is essential to maximize the educational benefits of YouTube while minimizing its potential negative impacts on elementary school students.